Parents' Understanding of Junk Food Through Nutrition Education Content - Oktami, Khaisya Nabila; Latifah, Nur Laila; Gustina, Lisna; Susanti, Rikza Azharona (Proceeding of International Conference on Islamic Education (ICIED), 2025)
This research is motivated by the increase in junk food consumption among children which is influenced by practicality, taste, and media exposure factors. This condition causes nutritional and health problems, so educational efforts are needed to increase parents' understanding of healthy eating. This study aims to describe parents' understanding of junk food and the role of digital nutrition education content in increasing nutrition awareness. The method used was a descriptive quantitative research with a survey technique using a questionnaire distributed to 135 parents in RW 06. Sawojajar Village, Kedungkandang District, Malang City. The data was analyzed statistically descriptive to see the level of parental understanding and the influence of exposure to nutrition education content on social media. The results of the study showed that the majority of respondents understood the negative impact of junk food on health, especially the risk of obesity and heart disease, and began to try to replace junk food with healthy home-made food. Most of the respondents also actively access nutrition education content through social media such as TikTok and Instagram, which have been proven to be effective in increasing nutrition knowledge and awareness. In conclusion, digital nutrition education content plays an important role in shaping parents' positive understanding and behavior towards a healthy diet for families. These findings confirm the importance of strengthening nutritional literacy through digital media as a preventive strategy to build healthy eating habits from an early age.